Topologically Guided Prioritization of Candidate Gene Transcripts Coexpressed with the 5-HT1A Receptor by Combining In Vivo PET and Allen Human Brain Atlas Data. (16th January 2020) - Unterholzner, Jakob; Gryglewski, Gregor; Philippe, Cecile; Seiger, Rene; Pichler, Verena; Godbersen, Godber M; Berroterán-Infante, Neydher; Murgaš, Matej; Hahn, Andreas; Wadsak, Wolfgang; Mitterhauser, Markus; Kasper, Siegfried; et al.
Abstract: The serotonin-1A receptor (5-HT1A R) represents a viable target in the treatment of disorders of the brain. However, development of psychiatric drugs continues to be hindered by the relative inaccessibility of brain tissue. Although the efficacy of drugs selective for the 5-HT1A R has not been proven, research continues to focus on drugs that influence this receptor subtype. To further knowledge on this topic, we investigated the topological coexpression patterns of the 5-HT1A R. We calculated Spearman's rho for the correlation of positron emission tomography-binding potentials (BPND ) of the 5-HT1A R assessed in 30 healthy subjects using the tracer [ carbonyl- 11 C]WAY-100635 and predicted whole-brain mRNA expression of 18 686 genes. After applying a threshold of r  > 0.3 in a leave-one-out cross-validation of the prediction of mRNA expression, genes with ρ ≥ 0.7 were considered to be relevant. In cortical regions, 199 genes showed high correlation with the BPND of the 5-HT1A R, in subcortical regions 194 genes. Using our approach, we could consolidate the role of BDNF and implicate new genes ( AnxA8, NeuroD2 ) in serotonergic functioning. Despite its explorative nature, the analysis can be seen as a gene prioritization approach to reduce the number of genes potentially connected to 5-HT1A R functioning and guide future in vitro studies.